Towards Climate-Smart Agriculture in Southeast Asia: Initial results in Ma Village, Vietnam - Vernooy, Ronnie; Hoang, Thi Lua (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
The project Integrated agricultural technologies for enhanced adaptive capacity and resilient livelihoods in climate-smart villages (CSVs) of Southeast Asia aims to provide climate-smart agriculture options to enhance adaptive capacity and resilience among CSV farmers and stakeholders. The project is supported by a monitoring and evaluation (M&E) plan that has two broad dimensions: a technical one that deals with the biophysical research results and a social one that deals with how they key actors involved in the research experience progress, costs and benefits, achievements and challenges. A first M&E field mission to Ma village, Vietnam, at the end of 2016 used qualitative methods to assess initial progress of the social dimension. Ma women and men farmers are satisfied with emerging results of most of the introduced climate-smart practices and highly appreciative of the collaborative approach. Full adoption will increase efficiency of resource use within the farm and could contribute to increased farm productivity and income of households. However, in order to promote wide-scale adoption of these practices, a well-thought out-scaling strategy should be designed and implemented.